Evaporation induced convection enhances mixing in the upper ocean - Falor, Devang; Gayen, Bishakhdatta; Sengupta, Debasis; Ivey, Gregory N. (Frontiers in Marine Science, 2023)
The upper ocean surface layer is directly affected by the air-sea fluxes. The diurnal variations in these fluxes also cause the upper ocean mixed layer turbulence and mixing to diurnally vary. The underlying thermohaline structure also varies accordingly throughout the day. Here we use large-eddy simulation to quantify the role of surface evaporation in modulating the diurnal mixed layer turbulence and mixing in the presence of wind forcing. During daytime, the upper ocean boundary layer becomes thermally stratified, and a salinity inversion layer is formed in the upper 10m, leading to double diffusive salt-fingering instability. During nighttime, the mixed layer undergoes convective deepening due to surface buoyancy loss redfrom both surface cooling and evaporation. We find that salinity makes a major contribution to the convective instability during both transitions between day and night. Overall surface evaporation increases the mixed layer depth and irreversible mixing through convection, both during nighttime and daytime, and leads to better prediction of the dynamical variables as sea surface salinity (SSS) and sea surface temperature (SST). Our findings can help improve the ocean parameterizations to improve the forecasts on a diurnal timescale.